Vision and challenges of a cartographic representation of expert medical centres for rare diseases - Storf, Holger; Ückert, Frank (E-Health - for continuity of care, 2014)
In Germany, many highly specialized facilities for the diagnosis and treatment of rare diseases exist. However it is quite difficult for patients to find the required specialists because of the fact that information on the internet is scattered and of variable quality. The German Federal Ministry of Health initiated several activities to address this issue. This paper describes the project se-atlas which aims at presenting the medical care options for people with rare diseases on an interactive map and in a list format. Potential users of this resource will be patients and their relatives, doctors, non-medical personnel and the general public. Most information derived from the data sets is already listed in ORPHANET. The project's primary goals are to steadily increase the data set and to ensure its quality. This paper presents the goals and measures taken in this project. It gives an overview of the challenges implementing such a new service and the visions behind.